2017
DOI: 10.1002/14651858.cd004143.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hormone therapy for perimenopausal and postmenopausal women

Abstract: BACKGROUND: Hormone therapy (HT) is widely provided for control of menopausal symptoms and has been used for the management and prevention of cardiovascular disease, osteoporosis and dementia in older women. This is an updated version of a Cochrane review first published in 2005. OBJECTIVES: To assess effects of long-term HT (at least 1 year's duration) on mortality, cardiovascular outcomes, cancer, gallbladder disease, fracture and cognition in perimenopausal and postmenopausal women during and after cessatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
324
2
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(352 citation statements)
references
References 227 publications
5
324
2
21
Order By: Relevance
“…The health benefits were seen up to 6 years after stopping. 2012 Cochrane collaboration systemic review 11 assessed the clinical effects of using HRT for 1 year or more. Twenty three randomized double blind studies were included involving 42830 women aged 26-91 yrs.…”
Section: Effect Of Hrt On Cardiovascular Events In Recently Post Menomentioning
confidence: 99%
“…The health benefits were seen up to 6 years after stopping. 2012 Cochrane collaboration systemic review 11 assessed the clinical effects of using HRT for 1 year or more. Twenty three randomized double blind studies were included involving 42830 women aged 26-91 yrs.…”
Section: Effect Of Hrt On Cardiovascular Events In Recently Post Menomentioning
confidence: 99%
“…The most widely used treatment for menopause-related changes is hormone replacement therapy with estrogen, progestin, and their derivatives [14,15]. Hormone replacement therapy has been shown to reduce such symptoms as bone loss, hot lashes, irritability, and mood swings [16,17] and improve overall mental health [7]. Nevertheless, hormone replacement therapy also has side efects that restrict its long-term use in some women [18,19].…”
Section: A Multidisciplinary Look At Menopausementioning
confidence: 99%
“…In the past, several studies have shown benefits of estrogen (and progesterone) use [1,2], or lack of cancer risk [3], while others have shown a relative increased risk [4][5][6]. Multiple etiologies, in addition, have been posited in regard to other malignances.…”
Section: Introductionmentioning
confidence: 99%